PENYULUHAN PEKAN IMUNISASI NASIONAL POLIO UNTUK PENCEGAHAN PENYAKIT POLIO DI DESA GANDARIA - Desiyani, Risma Eka; Agustiansyah, Lucky Dita; Endrawati, Santi; Hotimah, Novia Husnul (LPPM Universitas Bina Bangsa, 2025)
Basic immunization is the provision of initial immunization to infants to achieve immunity levels above the protection threshold. Types of basic immunization, namely: BCG, Hepatitis B, DPT, and Polio. Polio can easily be transmitted to children, polio is a disease that attacks the nerves and the worst impact can cause permanent paralysis. The National Immunization Week (PIN) program is held simultaneously in all regions, there are two stages: the first round of PIN starts from July 23 to July 29, 2024, while the second round of PIN starts from August 6 to August 17, 2024. Mothers' knowledge and education will affect their behavior in providing immunization to infants and children, so that it can affect their immunization status. PMT aims to improve the condition of vulnerable groups suffering from malnutrition, especially toddlers